A Market-Based Heuristic Algorithm for the Expansion Planning of the High Voltage Transmission Systems - Hesamzadeh, M.; Hosseinzadeh, N.; Wolfs, Peter (IREE, 2008)
The worldwide trend for the restructuring of electric industry has caused dramatic changes in operation and planning procedures of the power system. Under the restructured electricity market environment, identifying a minimum-cost plan under particular constraints is not sufficient anymore and other aspects such as market efficiency and environmental concerns are of equal importance. In this context, network augmentation plays a vital role in providing a full competitive environment for market players. This paper presents a novel forward heuristic algorithm to select the most effective expansion options based on a set of market-based and reliability-based sensitivity indices. These indices are used for multi-evaluation of each transmission option from the view point of electricity market and reliability criteria. The proposed method has been applied on a 6-bus test system for verifying its effectiveness.